Possible mechanisms responsible for absence of a retrotransposon family on a plant Y chromosome. Issue 2 (23rd January 2014) - Kubat, Zdenek; Zluvova, Jitka; Vogel, Ivan; Kovacova, Viera; Cermak, Tomas; Cegan, Radim; Hobza, Roman; Vyskot, Boris; Kejnovsky, Eduard
Summary Some transposable elements (TEs) show extraordinary variance in abundance along sex chromosomes but the mechanisms responsible for this variance are unknown. Here, we studied Ogre long terminal repeat (LTR) retrotransposons in Silene latifolia, a dioecious plant with evolutionarily young heteromorphic sex chromosomes. Ogre elements are ubiquitous in the S. latifolia genome but surprisingly absent on the Y chromosome. Bacterial artificial chromosome (BAC) library analysis and fluorescence in situ hybridization (FISH) were used to determine Ogre structure and chromosomal localization. Next generation sequencing (NGS) data were analysed to assess the transcription level and abundance of small RNAs. Methylation of Ogres was determined by bisulphite sequencing. Phylogenetic analysis was used to determine mobilization time and selection forces acting on Ogre elements. We characterized three Ogre families ubiquitous in the S. latifolia genome. One family is nearly absent on the Y chromosome despite all the families having similar structures and spreading mechanisms. We showed that Ogre retrotransposons evolved before sex chromosomes appeared but were mobilized after formation of the Y chromosome. Our data suggest that the absence of one Ogre family on the Y chromosome may be caused by 24‐nucleotide (24‐nt) small RNA‐mediated silencing leading to female‐specific spreading. Our findings highlight epigenetic silencing mechanisms as potentially crucial factors in sex‐specific spreading of some TEs, but other possible mechanisms are also discussed.